Saber pro tests in business administration programs in Colombia - Sierra Umaña, Yeiny Liset; Gómez Ramírez, Diana Marcela; Bayona Albarracín, Johana Alexandra (Cuadernos de Administración, 2022)
This research analyzes the Saber Pro tests of the Business Administration programs in Colombia through a descriptive study with a quantitative approach based on secondary data. The results of the generic and specific competencies evaluated in the Saber Pro tests in the years 2016 to 2020 exposed by the ICFES were considered. As population and sample, 184 Business Administration programs were taken for the years 2016, 181 (2017), 177 (2018), 185 (2019) and 174 (2020). The findings show that in generic competencies the lowest results were associated with citizenship competencies, written communication, and quantitative reasoning. Regarding specific competencies, the lowest performance results were financial and organizational management. This panorama casts doubt on the quality of business administration programs and calls upon Institutions of Higher Education (IHEs) to seek the development of competencies in their students that will guarantee them the adequate exercise of their profession.